Model Pemberdayaan Ekonomi Melalui Kewirausahaan Digital untuk Menyeimbangkan Tekanan Domestik Perempuan Jawa Sebagai "Konco Wingking" dan Tuntutan Dual Earner Family - Savitri, Maya Dewi; Djamil, Farah Diana; Tyas, Dyah Wahyuning (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Javanese women in Sleman Regency continue to face role conflict stemming from traditional expectations as “konco wingking” (a term denoting their prescribed role within the domestic sphere) and the increasing demands of dual-earner family structures that necessitate public engagement. Despite the enduring influence of conventional gender norms, a significant number of women engaged in micro-entrepreneurial activities have successfully contributed to household income, mitigated economic burdens, and achieved greater financial independence. This study seeks to formulate a strategic model for economic empowerment through digital entrepreneurship within the tourism sector, aiming to foster a balanced integration between women's domestic responsibilities and public participation. Utilizing a mixed methods sequential explanatory approach, this study integrates quantitative data from 50 participants with qualitative insights derived from in-depth interviews with 30 informants. The findings indicate a marked gap between the participants’ limited digital entrepreneurial competencies and their considerable need for structured capacity-building initiatives. Nevertheless, the presence of robust familial support has played a pivotal role in enabling these women to manage and reconcile their domestic and public responsibilities. In response to these findings, the study proposes a holistic empowerment model that prioritizes digital skill development, institutional support mechanisms, and community-driven collaboration—aimed at strengthening women’s dual roles and promoting sustainable economic and social empowerment.